2012
DOI: 10.3390/ijerph9093286
|View full text |Cite
|
Sign up to set email alerts
|

Helmet Use and Associated Factors among Thai Motorcyclists during Songkran Festival

Abstract: The aim of this study was to assess helmet use and associated factors among motorcycle riders during Songkran festival in Thailand. A cross-sectional survey was conducted to determine the prevalence of helmet use among Thai motorcycle riders (sample size = 18,998) during four days of the Songkran festival. For this sample, the population of motorcycle riders was consecutively selected using quota sampling from 12 petrol stations in four provinces from each of the four main geographical regions of Thailand. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 30 publications
4
43
1
Order By: Relevance
“…Similar findings were reported in studies done by Siviroj and Reang that 67.3% were males and 32.7% were females. 10,11 Awareness of road safety measures among the participants was high in our study. This may be due to increase in the awareness activities through mass media.…”
Section: Discussionmentioning
confidence: 59%
“…Similar findings were reported in studies done by Siviroj and Reang that 67.3% were males and 32.7% were females. 10,11 Awareness of road safety measures among the participants was high in our study. This may be due to increase in the awareness activities through mass media.…”
Section: Discussionmentioning
confidence: 59%
“…A Study in reported that 67.3% were males and 32.7% were females. 3,7 Table 1 outlines the socio-demographic profile of the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to in current study selected participants were pre-final and final year undergraduate students and Ratna et al selected 1st year to final year undergraduate students. 7 The majority of the participants were males (67.5%) and 37.5% were females. 7 The same distribution of participants observed by Ron et al and Ratna et al in the present study regarding behavioral patterns, 12% were involved in drunken driving.…”
Section: Discussionmentioning
confidence: 94%
“…7 The majority of the participants were males (67.5%) and 37.5% were females. 7 The same distribution of participants observed by Ron et al and Ratna et al in the present study regarding behavioral patterns, 12% were involved in drunken driving. 8,9 These findings were similar to the observation in the study conducted by Swamy et al in Chandigarh.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation